Vulnerabilities in child well-being among primary school children: a cross-sectional study in Bradford, UK. Issue 6 (30th June 2022) - Pickett, Kate E; Ajebon, Mildred; Hou, Bo; Kelly, Brian; Bird, Philippa K; Dickerson, Josie; Shire, Katy; McIvor, Claire; Mon-Williams, Mark; Small, Neil; McEachan, Rosemary; Wright, John; et al.
Abstract : Objective: To describe the prevalence of factors related to well-being among primary school children in a deprived multiethnic community in the UK. Design and participants: Cross-sectional survey of 15 641 children aged 7–10 years in Born in Bradford's Primary School Years study: whole-classroom samples in 89 Bradford primary schools between 2016 and 2019. Main outcome measures: Prevalence estimates by ethnicity (%, 95% CI) of single and multiple vulnerabilities in child well-being within and across four domains (Home, Family, Relationships; Material Resources; Friends and School; Subjective Well-being). Results: Only 10% of children had no vulnerabilities in any domain of well-being; 10% had one or more vulnerabilities in all four domains. The highest prevalence estimates were for being bullied some or all of the time (52.7%, 95% CI: 51.9% to 53.4%), keeping worries to oneself (31.2%, 95% CI: 30.5% to 31.9%), having no park near home (30.8%, 95% CI: 30.1% to 31.5%) and worrying all the time about how much money their family has (26.3%, 95% CI: 25.6% to 27%). Boys were consistently significantly more likely than girls to report all of the vulnerabilities in the Home, Family and Family Relationships domain, and the majority of indicators in the other domains, and in all domains except Friends and School, boys were significantly more likely to have at least one vulnerability. Girls were significantly more likely to report not having many friends (16.7%, 95% CI: 15.9% to 17.6% vs 12.5%, 95% CI: 11.8% to 13.2%), being bullied some or all of the time (55.8%, 95% CI: 54.7% to 56.9% vs 49.7%, 95% CI: 48.6% to 50.8%) and feeling left out all the time (12.1%, 95% CI: 11.4% to 12.8%) versus (10.3%, 95% CI: 9.7% to 11.0%). Variations in vulnerabilities by ethnicity were complex, with children in black, Asian and minority ethnic groups sometimes reporting more vulnerabilities and sometimes fewer than white British children. For example, compared with children of Pakistani heritage, white British children were more likely to say that their family never gets along well (6.3%, 95% CI: 5.6% to 7.1% vs 4.1%, 95% CI: 3.6% to 4.6%) and to have no access to the internet at home (22.3%, 95% CI: 21% to 23.6% vs 18%, 95% CI: 17% to 18.9%). Children with Pakistani heritage were more likely than white British children to say they had no park near their home where they can play with friends (32.7%, 95% CI: 31.6% to 33.9% vs 29.9%, 95% CI: 28.6% to 31.3%), to report not having three meals a day (17.9%, 95% CI: 16.9% to 18.8% vs 11.9%, 95% CI: 10.9% to 12.9%) and to worry all the time about how much money their families have (29.3%, 95% CI: 28.2% to 30.3%) vs (21.6%, 95% CI: 20.4% to 22.9%). Gypsy/Irish Traveller children were less likely than white British children to say they were bullied some or all of the time (42.2%, 95% CI: 35.4% to 49.4% vs 53.8%, 95% CI: 52.3% to 55.3%), but more likely to say they were mean to others all the time (9.9%, 95% CI: 6.3% to 15.2% vs 4%, 95% CI: 3.5% to 4.7%) and can never work out what to do when things are hard (15.2%, 95% CI: 10.6% to 21.2% vs 9%, 95% CI: 8.2% to 9.9%). We considered six vulnerabilities to be of particular concern during the COVID-19 pandemic and associated national and local lockdowns: family never gets along well together; no garden where child can play; no nearby park where they can play; not having three meals a day; no internet at home; worried about money all the time. Pre-pandemic, 37.4% (95% CI: 36.6% to 38.3%) of Bradford children had one of these vulnerabilities and a further 29.6% (95% CI: 28.9% to 30.4%) had more than one. Conclusions: Although most primary school children aged 7–10 in our study had good levels of well-being on most indicators across multiple domains, fewer than 10% had no vulnerabilities at all, a worrying 10% had at least one vulnerability in all the four domains we studied and two-thirds had vulnerabilities of particular concern during the COVID-19 lockdowns.